Improvement of Immune Defense and Survival of Grouper Fish (Ephinepelus sp.) Using the Immuno-Probiosirkulasi System (SI-PBR) Method in Semi-Intensive Ponds in Brondong, Lamongan - Mahasri, Gunanti; Woro Hastuti Satyantini; Nina Nurmalia Dewi; Lia Oktavia Ika Putri; Lilis Cahaya Septiana; Elangga Sony Widiharsono; Salman Aldo Alfaresi; Faisol Mas’ud; Fuquh Rahmat Shaleh; M. Khairul Anam; Ika Purnamasari (Universitas Islam Lamongan, 2024)
Grouper (Epinephelus sp.) is a marine fishery commodity that is widely cultivated in marine cages and ponds. The export market demand for grouper fish continues to increase every year by 30.75% every year, so there is a need for improvement, through various technological applications. The main obstacle in cultivating grouper fish in ponds is the decline in water quality and disease attacks, which can cause up to 100% crop failure, just 3 – 5 days after infection. One effort that can be implemented is the cultivation method with the Immuno-Probiocirculation System (SIPBR). Brondong sub-district is one of the areas in Lamongan which has large fisheries potential, especially for breakwater water pools, which are the top among other districts. There have been many cases of grouper deaths in ponds to date, which are caused by disease attacks and water quality. The aim of this community service activity is to apply the Immuno-Probioculation System fish aquaculture technology in traditional plus pattern ponds (SI-PBR), increasing grouper fish production in Lamongan Regency, East Java. Observational method which includes socialization / counseling, planning and guidance for implementing SI-PBR technology in one period (three months). These results show positive indications. There is an increase in farmer knowledge, the SI-PBR method can reduce ectoparasite infestation and increase grouper yields from 272.43 kg / ha to 87.66 kg / ha, meaning an increase of 334%. The conclusion from this activity is that the SI-PBR model can increase fish production and can be applied in wider areas in the Lamongan region.